PRODUCTION OF RECOMBINANT HUMAN INTERFERON-GAMMA IN Escherichia coli - Mussakhmetov , A.; Turgimbayeva , A.; Khassenov , B. (Eurasian Journal of Applied Biotechnology, 2016)
Human interferon-gamma (IFN-γ) is an important immune component that protects against pathogens and tumours. The IFN-γ cytokine, the only member of the type II interferon family, is produced predominantly by natural killer (NK) and natural killer T (NKT) cells as part of the innate immune response, and by Th1 CD4 and CD8 cytotoxic T lymphocyte (CTL) effector T cells upon the development of antigen-specific immunity. The recombinant production of IFN-γ has significant practical value. Here, we describe the production of recombinant human IFN-γ, the gene of which (hIFNG) was efficiently expressed in E. coli. The hIFNG gene was assembled from synthetic fragments, amplified by PCR, and subsequently cloned into several plasmid vectors. The target gene was cloned into recombinant vectors both with and without a hexa-histidine tag. The Rosetta2 (DE3) E. coli strain was used as the host strain for recombinant protein expression and high levels of synthesis of the recombinant human IFN-γ were achieved by the optimisation of induction conditions. The optimal concentration of isopropyl-β-D-thiogalactopyranoside (IPTG) was found to be 0.005 mM. The recombinant protein was shown to accumulate in the E. coli cells as inclusion bodies, and highly pure recombinant human IFN-γ was obtained by multi-stage extraction with chaotropic agents. Purification was carried out by a combination of anion and cation exchange chromatography using Q- and SP-sepharose.